Roles of dietary fibre and ingredient particle size in broiler nutrition. Issue 2 (1st June 2018) - Kheravii, S.K.; Morgan, N.K.; Swick, R.A.; Choct, M.; Wu, S.-B.
Abstract : Increasing the structural components in the diet, namely through including coarse grain particles in diets and manipulating the dietary fibre composition, has been shown to improve gut health, feed utilisation and production efficiency. This is primarily because structural components physically stimulate activity in the fore gut. An example of this is dietary non-starch polysaccharides (NSP), namely insoluble NSP, which have been shown to instigate beneficial effects on gut health, litter quality and nutrient utilisation, by increasing crop and gizzard activity, stimulating digestive enzyme production and enhancing bacterial fermentation in the hind gut. However, there is a lack of consistency with regard to the direct effects of dietary fibre on chicken health and production. The aim of this review therefore is to explore the impact of feeding different sources of fibre and different size grain particles on gut health and microflora, nutrient utilisation, performance and litter quality in broilers.